2014
DOI: 10.1186/1758-5996-6-99
|View full text |Cite
|
Sign up to set email alerts
|

Association of adipokines, leptin/adiponectin ratio and C-reactive protein with obesity and type 2 diabetes mellitus

Abstract: ObjectiveAlterations in plasma adipokines and/or inflammatory parameters in Type 2 DM remain vague as to whether they are due to obesity and/or directly associated with the diabetic state. Our objective was to compare plasma adiponectin, leptin, leptin/adiponectin ratio (LAR) and hs-CRP in obese non-diabetic subjects and non-obese Type 2 DM patients, as well as determining the association of these adipokines with MetS and diabetes-related quantitative traits.MethodsIn this study, 92 Yemeni male volunteers aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
78
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 55 publications
(79 reference statements)
13
78
3
1
Order By: Relevance
“…Indeed leptin levels were negatively associated with HbA1c in our study. Other studies also reported a relationship between leptin levels and glucose metabolism . However, because leptin levels were lower in children with T1DM as compared with children with T2DM , this finding points against a direct relationship between hyperglycemia and leptin levels.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed leptin levels were negatively associated with HbA1c in our study. Other studies also reported a relationship between leptin levels and glucose metabolism . However, because leptin levels were lower in children with T1DM as compared with children with T2DM , this finding points against a direct relationship between hyperglycemia and leptin levels.…”
Section: Discussionmentioning
confidence: 94%
“…However, previous epidemiological studies investigating the association between circulating leptin levels and incident of T2DM yielded discrepant results (12,13). Some studies have reported reduced leptin concentrations in T2DM (14), whereas others reported increased leptin levels (15)(16)(17) or no difference of leptin levels between obese humans with and without T2DM (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin and CRP are independent risk factors of CVD, together serve a synergistic role in metabolic regulation in the general population and T2D subjects [35][36][37] . We found that AA women with high adiponectin and low CRP levels, which translated into a high ratio, had significantly lower FG, IN, HOMA-IR, WC, %BF and BMI relative to those with a low ratio.…”
Section: Comparedmentioning
confidence: 99%
“…In addition, reasons for the elevated TSH levels among diabetics are still uncertain. Previous studies suggested that leptin levels were higher in diabetics [22], which might stimulate TSH synthesis via the HPT axis. Therefore, a decline in TSH release and FT 3 /FT 4 concentrations may contribute to the compensatory reductions in energy expenditure and catabolism that typically accompany weight loss and diabetes remission induced by RYGB.…”
Section: Discussionmentioning
confidence: 99%